Design and in vitro/in vivo evaluations of a multiple-drug-containing gingiva disc for periodontotherapy. Issue 14 (27th February 2020) - Jain, Pooja; Mirza, Mohd. Aamir; Talegaonkar, Sushama; Nandy, Shyamasree; Dudeja, Mridu; Sharma, Nilima; Anwer, Md. Khalid; Alshahrani, Saad M.; Iqbal, Zeenat
Abstract : A gingiva disc of cellulose acetate phthalate and poloxaner F-127 was developed for the simultaneous delivery of multiple drugs, including minocycline, to promote alveolar bone regeneration by abolishing infection, impeding inflammation and averting collagen destruction. Abstract : In the current work, we set out to develop and evaluate a gingiva disc of cellulose acetate phthalate and poloxamer F-127 for the simultaneous delivery of multiple drugs, namely minocycline, celecoxib, doxycycline hyclate, and simvastatin, to abolish infection, impede inflammation, avert collagen destruction, and promote alveolar bone regeneration, respectively. In vitro release studies revealed the sustained release profiles of the drugs for 12 h and that they were active against Staphylococcus aureus, Escherichia coli and Streptococcus mutans. The in vivo bioactivity levels of these drugs were assessed by comparing the number of colony forming units during different phases of a study on Wistar rats, and the results showed a reduction in the number of bacterial colonies with the applied formulation. A mucosal irritation study conducted on Wistar rat gingiva confirmed the non-irritancy of the optimal gingiva disc. Hence, this customized, non-invasive polymeric gingiva disc displaying a sustained release of drugs can be a useful tool to treat acute to moderate stages of periodontitis.